Chromothripsis as a pathogenic driver of multiple myeloma. (March 2022) - Maura, Francesco; Boyle, Eileen M.; Rustad, Even H.; Ashby, Cody; Kaminetzky, David; Bruno, Benedetto; Braunstein, Marc; Bauer, Michael; Blaney, Patrick; Wang, Yubao; Ghamlouch, Hussein; Williams, Louis; et al.
Abstract: Analysis of the genetic basis for multiple myeloma (MM) has informed many of our current concepts of the biology that underlies disease initiation and progression. Studying these events in further detail is predicted to deliver important insights into its pathogenesis, prognosis and treatment. Information from whole genome sequencing of structural variation is revealing the role of these events as drivers of MM. In particular, we discuss how the insights we have gained from studying chromothripsis suggest that it can be used to provide information on disease initiation and that, as a consequence, it can be used for the clinical classification of myeloma precursor diseases allowing for early intervention and prognostic determination. For newly diagnosed MM, the integration of information on the presence of chromothripsis has the potential to significantly enhance current risk prediction strategies and to better characterize patients with high-risk disease biology. In this article we summarize the genetic basis for MM and the role played by chromothripsis as a critical pathogenic factor active at early disease phases. Graphical Abstract: ga1